HCV resistance compartmentalization within tumoral and non‐tumoral liver in transplanted patients with hepatocellular carcinoma. (16th July 2019) - Sorbo, Maria C; Carioti, Luca; Bellocchi, Maria C; Antonucci, FrancescoPaolo; Sforza, Daniele; Lenci, Ilaria; Ciancio Manuelli, Matteo; Armenia, Daniele; De Leonardis, Francesco; Milana, Martina; Manzia, Tommaso M; Angelico, Mario; et al.
Abstract: Background & aims: We investigated the HCV‐RNA amount, variability and prevalence of resistance‐associated substitutions (RASs), in plasma, hepatic tumoral and non‐tumoral tissue samples in patients undergoing liver‐transplant/hepatic‐resection (LT/HR), because of hepatocellular carcinoma and/or cirrhosis. Methods: Eighteen HCV‐infected patients undergoing LT/HR, 94.0% naïve to direct‐acting antivirals (DAAs), were analysed. HCV‐RNA was quantified in all compartments. NS3/NS5A/NS5B in plasma and/or in tumoral/non‐tumoral tissues were analysed using Sanger and Ultra‐deep pyrosequencing (UDPS, 9/18 patients). RASs prevalence, genetic‐variability and phylogenetic analysis were evaluated. Results: At the time of LT/HR, HCV‐RNA was quantifiable in all compartments of DAA‐naïve patients and was generally lower in tumoral than in non‐tumoral tissues (median [IQR] = 4.0 [1.2‐4.3] vs 4.3[3.1‐4.9] LogIU/µg RNA; P  = 0.193). The one patient treated with sofosbuvir + ribavirin represented an exception with HCV‐RNA quantifiable exclusively in the liver, but with higher level in tumoral than in non‐tumoral tissues (51 vs 7 IU/µg RNA). RASs compartmentalization was found by Sanger in 4/18 infected‐patients, and by UDPS in other two patients. HCV‐compartmentalization resulted to be associated with HBcAb‐positivity ( P  = 0.013). UDPS showed approximately higher genetic‐variability in NS3/NS5A sequences in all compartments. Phylogenetic‐analysis showed defined and intermixed HCV‐clusters among/within all compartments, and were strongly evident in the only non‐cirrhotic patient, with plasma and non‐tumoral sequences generally more closely related. Conclusions: Hepatic compartments showed differences in HCV‐RNA amount, RASs and genetic variability, with a higher segregation within the tumoral compartment. HBV coinfection influenced the HCV compartmentalization. These results highlight HCV‐strain diversifications within the liver, which could explain some of the failures occurring even today in the era of DAAs.